G108 Early life constipation has a strong heritable component and hard stools can precede fibre intake and predict a subsequent low fibre diet. (May 2019) - Tappin, DM; Grzeda, M; Joinson, C; Heron, J
Abstract : Aim: The aim was to answer the research question: Does a low fibre diet cause constipation in children? Methods: Traditional twin study methodology compared monozygous and dizygous twin pairs for concordance for constipation and it's precursor hard stools from 3 data sources. A UK cohort study had 72 twin pairs with zygosity and data on stool consistency at age 6 months, 2.5 years and 3.5 years. Published data from a US study included 338 twin pairs age 6–19 years and data on parent reported constipation. The UK twin study included 2267 twin pairs with data on self reported constipation and zygosity from 18 to 92 years. These latter data were arbitrarily divided into age groups 10–39 years, 40–59 years and greater than 60 years. A large cohort study of children was examined to ascertain which came first, constipation and its precursor hard stools, or fibre in the diet. Parent questionnaire included stool consistency at 4 weeks (n=6, 796–49% of whole cohort), 6 months (n=9, 828–70% of cohort), 2.5 years (n=9452%–68%) and parentally reported constipation age 4–10 years (n=8, 401–60%). These data were all linked to fibre intake at age 2 years. Results: Genetic predisposition explained 100% of hard stools at 6 months and 2.5 years, 66% at 3.5 years, as well as 63% of constipation at 6–19 years, 18% at 18–39 years, 23% age 40–59 years and 6%>60 years. Hard stools, predated fibre in the diet at infant age 4 weeks and at 6 months predicted a lower fibre intake at 2 years (p=0.003). Conclusion: For infants and children the major cause of hard stools and constipation appears to be genetic predisposition. A low fibre diet and constipation may be driven by hard stools causing parents to select a low fibre diet that their child will readily eat rather than the traditionally accepted opposite direction for causation. Prolonged effective medical treatment of hard stools in early childhood may increase fibre intake and reduce later chronic idiopathic constipation.